AQUA ROVER - Vengaloor, Reshma P.; Raju, Ashrith Sriram; Ajay, Aparnna; Dhanush, S.; Sandhiya, D. Jessica (Journal of Electronics and Informatics, 2022)
Water has been stated as one of the fundamental elements for the existence of life on Earth, and is being contaminated as a sign of human development and negligence towards the ecosystem. In spite of many waste disposal methodologies that have been proposed and brought into practice, the pollution rate is not differentiable. Around 80% of the Indian local body water sources have been reported as tainted due to waste dumping. Every year, around 1.5 million Indian children die from diarrhea. While looking at the water pollutants, plastic has a significant contribution towards this. They pile up, creating a layer on the water surface resisting the light to enter the water; also, the chemicals used in coating the plastic objects turn out to be life threatening for the aquatic lives as well as human lives. A considerable population use these local water body sources for drinking purposes and it adds up to the responsibility for us to keep them hygienic and safe. Many methods for abreaction have been initiated by the Government and other resources. This paper proposes an efficient, cost-effective, simple and habitat-friendly "AQUA ROVER" (prototype) which is a dedicated device to this concern.